Application of Carbon-Isotope-Logging Technology in High-Temperature and High-Pressure Wells: A Case Study of the Ledong Gas Field in the Yinggehai Basin - Heng Geng; Xiaojun Xin; Leli Cheng; Jiarong Su; Yitao Hu; Ting Song; Ruike Wang; Yongkang Li (Energies)
Carbon isotope logging technology can obtain timely and accurate hydrocarbon fluid and reservoir geological information and has great application potential in oil–gas body property analysis, the comprehensive study of source rocks, and fault-sealing evaluation. Since 2014, real-time methane isotope logging technology has been applied in the western South China Sea. Based on the on-site, real-time, continuous, and accurate detection of methane carbon isotopes, combined with the rapid comprehensive analysis and evaluation of logging gas measurement data, the application effect in ultra-high-temperature and high-pressure wells in the western South China Sea has been remarkable. Taking the Ledong 10 Area of Yinggehai Basin as an example, real-time carbon isotope logging data can be used to quickly identify gas origins, source rock maturity, and gas source type and help judge the sealing quality of overburdened mudstone caps. This knowledge can serve as a reference for ascertaining the popularity of isotope-logging technology in other areas.